PELATIHAN TEKNIK PEMBUATAN AKTA TERHADAP ANGGOTA LUAR BIASA PENGURUS WILAYAH RIAU INI - Satrio Abdillah; Nurhan (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2023)
This education and training activity for prospective Notaries is a routine agenda of the Central Board of the Indonesian Notary Association which is delegated through the Provincial Regional Managers, in order to prepare noble expertise and ethics for prospective Notaries who will later be appointed as Notary Professions and Positions. february 25, 2023 at the Khas Pekanbaru hotel which was attended by 59 participants in which the prospective Notary was called an Extraordinary Member (ALB). This activity was carried out due to the lack of study hours that ALB received when they held a notary level education so that additional training instruments were needed to improve the quality produced after ALB was actually appointed as a Notary who was Professional, reliable, moral and had integrity.